2022
DOI: 10.3390/ijms23020752
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Non-Coding RNAs during Tissue-Injury Associated Pain

Abstract: While about half of the population experience persistent pain associated with tissue damages during their lifetime, current symptom-based approaches often fail to reduce such pain to a satisfactory level. To provide better patient care, mechanism-based analgesic approaches must be developed, which necessitates a comprehensive understanding of the nociceptive mechanism leading to tissue injury-associated persistent pain. Epigenetic events leading the altered transcription in the nervous system are pivotal in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 164 publications
0
7
0
Order By: Relevance
“…The decrease of PV’s activity is not associated with a significantly diminished activity of the Pa, and thus we can presume the stress-response remains unaltered in the different genotypes and groups. Although this has not been assessed in the present study, a feasible association derived from the diminished activity of the PV observed in these Mecp2 -null mice and unrelated to stress-reactivity, could be the altered visceral and neuropathic pain responses ( Liang et al, 2020 ; Vigli et al, 2021 ; Irfan et al, 2022 ), which have been previously reported in heterozygous females ( Samaco et al, 2013 ). Similarly, altered pain perception, including visceral, has been documented in RTT ( Barney et al, 2015 ).…”
Section: Discussionmentioning
confidence: 73%
“…The decrease of PV’s activity is not associated with a significantly diminished activity of the Pa, and thus we can presume the stress-response remains unaltered in the different genotypes and groups. Although this has not been assessed in the present study, a feasible association derived from the diminished activity of the PV observed in these Mecp2 -null mice and unrelated to stress-reactivity, could be the altered visceral and neuropathic pain responses ( Liang et al, 2020 ; Vigli et al, 2021 ; Irfan et al, 2022 ), which have been previously reported in heterozygous females ( Samaco et al, 2013 ). Similarly, altered pain perception, including visceral, has been documented in RTT ( Barney et al, 2015 ).…”
Section: Discussionmentioning
confidence: 73%
“…Although there are some studies on epigenetics in RA, they are not systematic and do not deeply investigate the specific roles of different epigenetic regulators in RA 13,14 . Noncoding RNA and DNA demethylation are two main categories of epigenetic regulation 15–18 . In the current study, we found that three epigenetic regulators, miRNA‐22 (MIR22), ten‐eleven translocation methylcytosine dioxygenase 3 (TET3), and pseudogene MT‐RNR2 like 2 (MTRNR2L2), could simultaneously participate in the RA‐FLS–mediated inflammatory response.…”
Section: Introductionmentioning
confidence: 81%
“…13,14 Noncoding RNA and DNA demethylation are two main categories of epigenetic regulation. [15][16][17][18] In the current study, we found that three epigenetic regulators, miRNA-22 (MIR22), teneleven translocation methylcytosine dioxygenase 3 (TET3), and pseudogene MT-RNR2 like 2 (MTRNR2L2), could simultaneously participate in the RA-FLS-mediated inflammatory response.…”
Section: Introductionmentioning
confidence: 82%
“…However, microarrays use already known sequences, thus making them unsuitable for the discovery of novel ncRNAs. 23 , 24 …”
Section: Detection Methods Of Circulating Ncrnasmentioning
confidence: 99%